Reliability and availability analysis of the structural observability of bilinear systems: A graph-theoretical approach. (June 2014) - Dakil, Manal; Simon, Christophe; Boukhobza, Taha
This article deals with the reliability and the availability of the structural observability of bilinear systems using a graph-theoretical approach. The observability is a necessary property for the control, monitoring, and diagnosis of continuous systems. This property can be verified graphically. By linking the validation states of edges with the operating states of the system components, it is possible to express the satisfaction of the observability as a Boolean expression based on the operating state of the system components. In this work, we consider the failures of all the system components: internal and external (actuators/sensors). Using the Boolean expression, it is easy to obtain the corresponding Markov chain which allows us to compute the reliability/availability or the reliability of the property. The information on the reliability/availability of the observability allows us to predict the satisfaction of this property during the mission time of the system when one or more components fail. The proposed graphical approach considers only the knowledge of the system structure. Thus, the study can start at the early phases of the system life-cycle.